2011
DOI: 10.1038/aja.2010.159
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose testosterone treatment decreases oxidative damage in TM3 Leydig cells

Abstract: Testosterone replacement therapy has benefits for aging men and those with hypogonadism. However, the effects of exogenous testosterone on Leydig cells are still unclear and need to be clarified. In this report, we demonstrate that testosterone supplementation can reduce oxidative damage in Leydig cells. The TM3 Leydig cell line was used as an in vitro cell model in this study. Cytoprotective effects were identified with 100-nmol l 21 testosterone treatment, but cytotoxic effects were found with o500-nmol l 21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 31 publications
2
21
1
Order By: Relevance
“…In addition, low testosterone levels and obese insulin resistance are known as risk factors of cardiac dysfunction (Culic & Busic 2015) due mainly to increased oxidative stress (Hwang et al 2011) in the heart, and leading to depressed HRV (Brook et al 2010). Moreover, previous studies found the association of low testosterone and the increase in the reactive oxygen species (ROS) level (Pongkan et al 2015(Pongkan et al , 2016.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, low testosterone levels and obese insulin resistance are known as risk factors of cardiac dysfunction (Culic & Busic 2015) due mainly to increased oxidative stress (Hwang et al 2011) in the heart, and leading to depressed HRV (Brook et al 2010). Moreover, previous studies found the association of low testosterone and the increase in the reactive oxygen species (ROS) level (Pongkan et al 2015(Pongkan et al , 2016.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies demonstrated that either testosterone or vildagliptin exerted beneficial effects on cardiac function in HFO and NDO groups in a testosterone-deprived model (Pongkan et al 2015), obese-insulin resistance model (Apaijai et al 2012(Apaijai et al , 2014 and testosterone-deprived with obese-insulin resistance model (Francomano et al 2014), our study is the first to compare the efficacy of testosterone replacement and vildagliptin for their cardioprotection. Regarding the effects of testosterone replacement and vildagliptin on the suppression of mitochondrial ROS production and apoptosis, previous studies demonstrated that either testosterone (Hwang et al 2011, Zhang et al 2013, Pintana et al 2015 or vildagliptin (Avila Dde et al 2013, Apaijai et al 2014 could effectively reduce ROS generation and suppressed oxidative stress. In addition, Alessandro and coworkers reported that testosterone decreased ROS production by binding to cytoplasmic androgen receptor (AR) and promoting its translocation to the nucleus, resulting in enhanced extracellular matrix (ECM) production via the transcription-inducing complex c-FOS/c-JUN (Bertolo et al 2014).…”
Section: :1mentioning
confidence: 99%
“…This result is consistent with a previous clinical report in men with stable coronary artery disease (CAD) which demonstrated that a high level of blood testosterone was associated with reduced sympathovagal imbalance [ 37 ]. Since depressed HRV is known to be associated with increased oxidative stress [ 38 , 39 ] and that testosterone deprivation has been shown to affect the antioxidant defense system in the left ventricle (LV) [ 40 ] and associated with the increased oxidative stress [ 41 , 42 ], testosterone replacement could play a crucial role in the protection of cardiac sympathovagal imbalance by reducing the oxidative stress and the enhancing of the antioxidant defense system. This hypothesis is supported by the findings of this study that ORX rats had increased cardiac mitochondrial ROS production, and testosterone attenuated ROS level.…”
Section: Discussionmentioning
confidence: 99%
“…46 Additionally, low-dose testosterone treatment can decrease ROS production and subsequent oxidative damage in Leydig cells in vitro. 47 ROS generated both from normal metabolism and in the process of steroidogenesis in Leydig cells, followed by ageassociated degeneration and testicular steroidogenesis inhibition. Consistent with previous reports, we showed that ROS levels were increased in Leydig cells from aged rats.…”
Section: Discussionmentioning
confidence: 99%